Hydrogen peroxide mediates hyperglycemia-induced invasive activity via ERK and p38 MAPK in human pancreatic cancer - Li, Wei (Oncotarget, 2015)
Diabetes mellitus and pancreatic cancer are intimately related, as approximately 85% of pancreatic cancer patients suffer from glucose intolerance or even diabetes. In this study, we evaluate the underlying mechanism by which hyperglycemia modulates the invasive potential of cancer cells and contributes to their enhanced metastatic behavior. Here we show that hyperglycemia increases the hydrogen peroxide (H(2)O(2)) concentration through up-regulation of manganese superoxide dismutase (SOD2) expression, which further activates the ERK and p38 MAPK pathways, as well as the transcription factors NF-κB and AP-1, in a time-dependent manner. The invasion of pancreatic cancer cells resulting from the activation of the H(2)O(2)/MAPK axis under high glucose conditions is effectively inhibited by PD 98059 (ERK inhibitor), SB 203580 (p38 MAPK inhibitor), polyethylene glycol-conjugated catalase (PEG-CAT), or the siRNA specific to SOD2. In addition, streptozotocin-treated diabetic nude mice exhibit a stronger tumor invasive ability in renal capsule xenografts which could be suppressed by PEG-CAT treatment. Furthermore, the integrated optical density (IOD) of SOD2 and uPA stainings is higher in the tumor tissues of pancreatic cancer patients with diabetes compared with pancreatic cancer patients with euglycemia. Taken together, our results demonstrate that hyperglycemia enhances cell invasive ability through the SOD2/H(2)O(2)/MAPK axis in human pancreatic cancer. Thus, SOD2/H(2)O(2)/MAPK axis may represent a promising therapeutic target for pancreatic cancer patients combined with diabetes mellitus.